HRA and its Impact on Employees Performance: A Field Research in the Ministry of Education - Al-Kargoli, Ahmed Obaid Hussain; Al-Zubaidi, Ghani Dahham Tani (Journal of Economics and Administrative Sciences, 2021)
The research aims to determine the impact of Human Resources Accounting (HRA) on employee’s performance. The research’s problem was embodied in the lack of interest in HRA, which was reflected on the performance of employees in the Ministry of Education; the research adopted the descriptive-analytical approach, and the research community included the directors of departments and people at the headquarters of the Ministry of Education. The sample size was (224) individuals from the total community of 533. The questionnaire was adopted as the main tool for collecting data and information, as well as the interviews that were conducted by the researcher. In order to analyze the results of the field research, the researcher adopted a program )Spss.v26) and included the search main premise and three sub-hypotheses were represented by the relationships of influence. The data was statistically processed using several statistical methods including Mean, Standard Deviation, and Simple Linear Regression. The results of the research led to the acceptance of all the alternative hypotheses and the rejection of the null hypotheses that there is a lack of interest in HRA, and surely over their effect to HRA on the performance of employees at the Ministry of Education